The Effects from Physical Exercise on the Blood Glucose Levels, HbA1c and Quality of Life of Type 2 Diabetes Mellitus Patients: A Systematic Review - Novita Fajriyah; I Ketut Sudiana; Erna Dwi Wahyuni (Jurnal Ners, 2020)
Introduction: The present study aimed to analyze the effects of aerobic exercise, resistance and a combination of both on blood glucose levels, HbA1c and quality of life for patients with T2DM.Methods: This systematic review used PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analysis). Scopus, Science Direct and PubMed online databases were extensively searched, focusing on the last five years. The search utilized the phrases "diabetes," "physical exercise,” "glucose" and "quality of life." The inclusion criteria in the study regarding the literature was that it had to be an original article, that the source was a journal, that the article was in English and that it was available in full text.Results: We identified 1017 articles where 17 were considered to be relevant for this systematic review. The combination of resistance and aerobic physical exercise seems to have a greater impact on glucose, HbA1c and quality of life. Aerobic exercise, resistance exercise and a combination of both have benefits when it comes to reducing blood glucose levels and HbA1c, as well as improving the quality of life of patients with T2DM.Conclussion: The type and intensity of the exercise chosen for the management of T2DM must be adjusted to the clinical condition and the patient’s individual physical fitness